Mediation, remediation, and the dynamics of cultural memory - Erll, Astrid; Rigney, Ann (Media and cultural memory, 2009)
This collection of essays brings together two major new developments in cultural memory studies: firstly, the shift away from static models of cultural memory, where the emphasis lies on cultural products, in the direction of more dynamic models where the emphasis lies instead on the cultural and social processes involved in the ongoing production of shared views of the past; and secondly, the growing interest in the role of the media, and their role beyond that of mere storage, within these dynamics. The specific concern of this collection is linking the use of media to the larger socio-cultur.